The Issue of the Createdness of the Qur’an and Ibn Taymiyyah's Approaches to It - Seda Tigranyan (Banber Arevelagitut'yan Instituti)
Ibn Taymiyyah’s (1263-1328),  the prominent representative of the Hanbali Madhhab,  discussions on the issue of the Qur’an's createdness is part of his struggle against dangerous innovations (bid'a) in Islam. The emergence of the discussed question is associated with theological disputes between Muslims and Christians in the context of the expansion of the Caliphate, the rapid development of the Islamic community and clashes with other cultures. During the Abbasid Caliphate, such questions acquired a political connotation, and the answer options to them were imposed or prohibited at the state level. In his works, Ibn Taymiyyah attempts to clarify and substantiate the approaches of the Hanbali school of thought, freeing them from ambiguity.